Evaluation of the conventional test methods for diagnosis of methicillin-resistant staphylococcus aureus (MRSA) - Lee Hui, Hua (Universiti Sains Malaysia, 2008)
Methicillin-resistant Staphylococcus aureus (MRSA) is a multiple drug-resistant bacterium, which responsible for nosocomial and community-acquired infection. This study compared the mannitol salt agar-oxacillin (MSO), mannitol salt agar-cefoxitin (MSC), oxacillin resistance screening agar base (ORSAB), chromogenic agar medium (CHROMagar), and MRSA-screen latex agglutination test to mecA PCR method as the "gold standard" assay in order to determine the most simple, reliable and cost effective test method for diagnostic purpose. 58 MRSA strains were isolated form 144 samples collected from HUSM. The MSO, MSC, ORSAB, CHROMagar, and MRSA-screen gave sensitivity with 94%, 95%, 97%, 95% and 93% respectively, specificity with 98%, 87%, 97%, 95% and 99% respectively, positive predictive value (PPV) with 98%, 83%, 95%, 93% and 98% respectively, negative predictive value (NPV) with 95%, 96%, 98% 97% and 96% respectively, and cost with RM1.24, RM 1.38, RM 1.42, RM 8.50 and RM 12.50 respectively for one sample. All the test methods were agreed with PCR. In conclusion, ORSAB have the highest diagnostic value, followed by MSO, MRSA-screen, CHROMagar and lastly MSC. The MSO was the cheapest test method, followed by MSC, ORSAB, CHROMagar and then MRSA-screen. ORSAB can be the most suitable diagnostic test method with high diagnostic test value and low cost.